Anti-Epstein–Barr Virus Activities of Flavones and Flavonols with Effects on Virus-Related Cancers - Sherif T. S. Hassan (Molecules)
The Epstein–Barr virus (EBV), a member of the human gamma-herpesviruses, is intricately linked to various human malignancies. Current treatment options for EBV infection involve the use of acyclovir and its derivatives, which exhibit limited efficacy and are associated with drug resistance issues. Therefore, there is a critical need for new medications with more effective therapeutic actions and less susceptibility to resistance. This review explores the therapeutic promise of flavones and flavonols, naturally occurring molecules, against EBV and its correlated cancers. It thoroughly delves into the molecular mechanisms underlying the therapeutic efficacy of these compounds and scrutinizes their complex interplay in EBV-linked processes and cancer transformation by targeting key genes and proteins pivotal to both the viral life cycle and tumor development. Additionally, the review covers current research, highlights key findings, and discusses promising avenues for future investigations in the pursuit of targeted therapies against EBV and its related tumors.